Factorial analysis of xylanase and cellulase production from pineapple peel waste - Sivanesan, Pavethra; Zatul Iffah, Mohd Arshad; Jun Haslinda, Shariffuddin; Nasratun, Masngut; Norazwina, Zainol; Shalyda, Md Shaarani (Trans Tech Publications Ltd, 2022)
Pineapple wastes (skin, core and crown) are mainly composed of carbohydrates (cellulose, hemicellulose, and lignin). Non-starch polysaccharides (NSP) in feed are indigestible by the endogenous enzymes in poultry. Thus, exogenous enzymes (xylanase and cellulase) are required to overcome this problem. Due to high fiber content, pineapple wastes are unsuitable for animal feed. However, the fermented waste juice could be used to produce enzymes. The objective of this study is to produce xylanase and cellulase from the fermentation of pineapple waste using Lactobacillus casei (L. casei) bacteria inoculated from probiotic drink. The fermentation was performed using different screening parameters (incubation time, temperature, pH value and substrate concentration) according to Two-Level Full Factorial Design (FFD) by Design Expert. From this study, the incubation temperature and substrate concentration had the highest influence on the xylanase activity (39.82 U/mL) while the fermentation time and substrate concentration mostly affected the cellulase activity (8.05 U/mL). Meanwhile, the pH had the least influence on both enzyme activities. The pineapple waste at its best fermentation parameters not only offers an economical way of high enzyme production but also alleviates the agricultural waste disposal issue. Further optimization of the pineapple waste fermentation parameters is required though to maximize enzyme production.